2017
DOI: 10.1371/journal.pone.0173934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of functional sympathetic nervous system impairment of the liver and abdominal visceral adipose tissue on circulating triglyceride-rich lipoproteins

Abstract: BackgroundInterruption of sympathetic innervation to the liver and visceral adipose tissue (VAT) in animal models has been reported to reduce VAT lipolysis and hepatic secretion of very low density lipoprotein (VLDL) and concentrations of triglyceride-rich lipoprotein particles. Whether functional impairment of sympathetic nervous system (SNS) innervation to tissues of the abdominal cavity reduce circulating concentrations of triglyceride (TG) and VLDL particles (VLDL-P) was tested in men with spinal cord inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 66 publications
(59 reference statements)
1
28
0
Order By: Relevance
“…Using DXA, a recent study confirmed previous findings and showed that VAT volume was not different between persons with SCI above T4 compared to those with SCI below T5 [45]. Those with SCI below T5 experience elevated levels of TG and very-lowÀdensity lipoprotein cholesterol compared to those with SCI above T4 [45]. Contrary to findings in a rat model, an injury at T3 is likely to be accompanied by greater VAT acclamation than SCI at T10 [11].…”
Section: Hormonal Contribution To Gender Differences In Central Adiposupporting
confidence: 65%
See 1 more Smart Citation
“…Using DXA, a recent study confirmed previous findings and showed that VAT volume was not different between persons with SCI above T4 compared to those with SCI below T5 [45]. Those with SCI below T5 experience elevated levels of TG and very-lowÀdensity lipoprotein cholesterol compared to those with SCI above T4 [45]. Contrary to findings in a rat model, an injury at T3 is likely to be accompanied by greater VAT acclamation than SCI at T10 [11].…”
Section: Hormonal Contribution To Gender Differences In Central Adiposupporting
confidence: 65%
“…In a preliminary study, the level of injury between tetraplegia and paraplegia did not influence distribution of VAT or SAT CSA but did influence the metabolic profile in persons with SCI [10]. Using DXA, a recent study confirmed previous findings and showed that VAT volume was not different between persons with SCI above T4 compared to those with SCI below T5 [45]. Those with SCI below T5 experience elevated levels of TG and very‐low−density lipoprotein cholesterol compared to those with SCI above T4 [45].…”
Section: Discussionmentioning
confidence: 57%
“…In the current study, the association between VLDL-C and liver adiposity is exemplified by the positive relationship between FSF and non-HDL-C, which confirms previous reports in able-bodied individuals [ 47 , 48 ]. Although we did not measure VLDL-C separately from LDL-C, no relationship was observed between FSF and HDL-C or LDL-C, highlighting the importance of VLDL-C related to liver metabolism [ 49 ]. Surprisingly, there was no relationship between FSF and FFA in the current study, which is in contrast to previous studies of persons with NAFLD [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our present data suggest that the parasympathetic activity is not yet significantly altered because of any change in the sensitivity of the reflex bradycardia. Furthermore, it is well established in the literature that the increase in sympathetic activity induces an increase in plasma leptin (9) , dietary intakes (44,45) , adipose tissue (46,47) and IR (48,49) . In this way, in the present study, the increase in sympathetic activity must be involved in all cardio-metabolic alterations induced by the H diet of the progenitors that were transmitted to female and male F1H and F2H offspring.…”
Section: Discussionmentioning
confidence: 99%